The Dynamics of the Curriculum of Pesantren Al Mukhtariyah Sungai Dua Portibi, Padang Lawas Utara - Tiroilan Siregar (Journal of Islamic Education Research, 2022)
Contributions pesantren cottage in Indonesia to improve the quality of human resources is not in doubt. It can be seen from many pesantren cottage alumni who participated actively in the development of this nation. But there are also so much criticism of the weaknesses of the educational process at the school, especially in terms of the curriculum, for example, limitations and less actual of pesantren cottage curriculum. Starting from these criticisms, and an awareness and desire among boarding schools, the boarding school curriculum enrichment balance between religious sciences and general sciences are a must. With the integration of Islamic boarding school religious knowledge with general knowledge, it is hoped that pesantren alumni will be able to take part and compete in society. Not many researchers have explored the dynamics of the pesantren curriculum. The purpose of this research is to examine how the dynamics of curriculum Pesantren Cottage Al Mukhtariyah Portibi Sungai Dua North Padang Lawas regency. The study was carried out data collection and dug out of resources through interviews, and study documentation and field notes, observations set forth in the form of descriptions that were then analyzed using qualitative data analysis interactive model of Miles and Huberman. After the gathering and analysis of data, it indicated that at the beginning of the Pesantren Cottage of Al Mukhtariyah Sungai Dua Portibi from 1932 to 1948 in the period of Mr. Tuan Sheikh Mukhtar that the curriculum is applied is sourced to the kitab kuning.So also during the years 1948-1952 Mustafa Buya, there is no change, the curriculum in pesantren still use thekitab kuning, then Mr. Zaharuddin started during 1958 to 1989 still made the kitab kuning  the curriculum.However the early 1990s during the period of Mr. Zaharuddin  pesantren cottage began to include some general lessons for junior secondary level, Mr. Qomaruzzaman the next period where the yellow book as a source or reference in the teaching and learning process at the school has begun to diminish, and the other side to add general subjects, or in other words pesantren cottage Al Mukhtariyah already implementing the National Curriculum for the Department of Religion and Aliyah junior secondary school level, as well as the period of H. Mahmud Syahrijal still using the curriculum of the National Department of Religion.The conditions above shows that the dynamics curriculum at thepesantren cottage of Al-Mukhtariyah Sungai Dua North Padang Lawas.